2022
DOI: 10.1021/acs.jnatprod.2c00620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Anthocyanin Hirsutidin on Gastric Ulcers: Improved Healing through Antioxidant Mechanisms

Abstract: The goal of this study was to determine the effect of hirsutidin on ethanol-induced stomach ulcers in rats. Rats (n = 24 rats/group) were separated at random into the following groups: normal saline-treated (normal control), ethanol-treated (ethanol control), 10 mg/kg hirsutidin + ethanol-treated (hirsutidin 10), and 20 mg/kg hirsutidin + ethanol-treated (hirsutidin 20). All the groups received the respective treatment orally for 7 days. On day 7, i.e., after 24 h of fasting, except for the normal control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[ 10 ] An animal study reported that anthocyanin polyphyllin mitigated gastric ulcers and elevated the concentration of PGE2 in serum. [ 48 ] The expression of these 3 indicators was statistically markedly increased in both groups after treatment. Considering the mechanism of these 3 indicators, it can be concluded that Piwei Peiyuan Prescription improves symptoms and boosts gastrointestinal motility and mucosal repair.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] An animal study reported that anthocyanin polyphyllin mitigated gastric ulcers and elevated the concentration of PGE2 in serum. [ 48 ] The expression of these 3 indicators was statistically markedly increased in both groups after treatment. Considering the mechanism of these 3 indicators, it can be concluded that Piwei Peiyuan Prescription improves symptoms and boosts gastrointestinal motility and mucosal repair.…”
Section: Discussionmentioning
confidence: 99%
“…5,[9][10][11] Oxidative stress is implicated in gastrointestinal mucosal injury. 12,13 Controlling oxidative stress is essential for the treatment of this pathology. NRF2 is a crucial regulator of antioxidant factors and activation of NRF2 results in anti-ulcer effects.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed the hepatoprotective properties of hirsutidin by attenuating alcohol-induced oxidative stress in rodents and the antiulcer consequence of hirsutidin against ethanol-induced ulcers in rats via regulation of antioxidant mechanisms . There is no clear mechanistic role of hirsutidin but due to its strong antioxidant property, it may be essentially used in treating the disorders.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is believed that this skill serves as a protection against variability of illnesses brought on by ROS. 17 According to studies, dietary foods high in anthocyanins have positive impacts on several health issues, including cardiovascular health, 18,19 diabetes, 20 obesity, 20,21 bacterial infection, 22 cancer, 23 eye health, 24 and neurotoxicity. 25 A member of the chemical family known as anthocyanins, hirsutidin is an O-methylated anthocyanidin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation